Les pointes organiques aurignaciennes et moustériennes de Divje babe I, Slovénie - François Zoltán Horusitzky (Arheološki Vestnik, 2007)
The reconstruction of bone and antler points is the first step towards statistical enquiry into the totality of points in a region.There were two aims in this article. First, to note a method of reconstruction on the basis of buckling and calculation by strength of material. Secondly, with the reconstruction of the Divje babe points, a practical application is displayed. Many problems are explained, particularly those of multiple fractures and the base splitting diagnostics. The points of Divje babe have analogies among the Aurignacian points of Istállóskő and Dzeravá skala. The Mousterian points can be compared to some very old finds at Vogelherd and Lieglloch. These comparisons are of mutual use.The theoretical basis is accessible on the web site (Annexe Théorie: http://site.voila.fr/horusitzkymusic1). But theory can-not deal with the majority of situations, such as the variable sections of the points or eccentric impact or lack of rigidity in the hafting. Practical solutions are proposed to determine the zones of rupture and the length of the missing fragments. Nonetheless the method is not infallible: a level of competence by the archaeologist is required to define the initial conditions and to choose between the possible reconstruction options.